Jewish Law-Observance in Paul - Paul T. Sloan (Religions)
Several statements in Paul’s letters have led scholars to conclude that Paul was not Law-observant and that he was at best indifferent, if not antagonistic, to Jewish Law-observance. This article challenges these views by situating supposedly “negative” statements on the Law within Paul’s discourse on justification (Gal 2) and freedom from the Law of sin and death (Rom 7), and argues that aspects of 1 Cor 7, Gal 2–3, and Rom 3–4 imply Paul expected even believing Jews to remain Law-observant.